(3GdMGf GdShGLY Hjf GdHGOi hGdeQGLYs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s ((3eMeO Hf YHO GdHGbi GdHQdSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdHGQi CSjQ hHYO bO cfJ bOjekG cJGHi GdgOGjG hSejJg HGdeMGRGg s
(3BNQgG (B:s
(3jG ef SeG Hjf GdhQi bOQg GcTa dfG Yfg hYf CUdg GfJgi cJGH CdMGf GdShGLY s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(1143) s
Keywords: (3GdCOHs